Búsquedas avanzadas tipo grep de tesis realizadas en la ESPOL utilizando el paradigma map-reduce - Aragundi, Grace (2010)
Currently the amount of information stored by companies in their databases and through the Web, has grown dramatically, this has led to the need to implement alternative to traditional mechanisms, based on parallel processing. This document explains the implementation of an advanced search mechanism on the thesis and graduation projects in ESPOL, which is efficient and scalable, based on the Map Reduce paradigm and implemented on Hadoop framework, running on clusters raised with the distributed computing EC2 service of the Amazon Web Services (AWS). Tests were performed using different regular expressions, that enabled us to create queries with higher levels of complexity, making that the results generated through this application were fully representative of what is expected to find.